Linking Social Protection Schemes: The Joint Effects of a Public Works and a Health Insurance Programme in Ethiopia. Issue 2 (1st February 2020) - Shigute, Zemzem; Strupat, Christoph; Burchi, Francesco; Alemu, Getnet; Bedi, Arjun S.
Abstract: In developing countries and in particular in sub-Saharan Africa, social protection schemes tend to operate in silos. However, schemes targeting the same geographical areas may have synergies that have not yet been examined, and which are worth scrutinising. This paper contributes to this knowledge gap by examining the joint impacts of two social protection programmes in Ethiopia, that is, the Productive Safety Net Programme and a Community Based Health Insurance Scheme. Based on three rounds of individual level panel data and several rounds of qualitative interviews, we find that individuals covered by both programmes, as opposed to neither or only one of the two programmes, provide greater labour supply, have larger livestock holdings, and have a lower amount of outstanding loans. Furthermore, joint participation is associated with greater use of modern health care facilities as compared to participating only in the safety net programme. These results show that bundling of interventions enhances protection against multiple risks and that linking social protection schemes yields more than the sum of their individual effects.